Investigation of radiation induced static mode degradation in Yb-Ce co-doped pulsed fiber amplifiers. (October 2022) - Wang, Bo; Cao, Chi; Zhang, Zhilun; Liao, Shibiao; Zhang, Anjun; Zhang, Xu; Xing, Yingbin; Chen, Gui; Zhou, Jun; Dai, Nengli; Peng, Jinggang; Li, Haiqing; et al.
Highlights: The radiation induced static mode degradation (SMD) was discovered and studied. The threshold of SMD could be related with the composition of active fiber and increases with the increase of Ce. When the Ce concentration increased by 35.5%, SMD threshold rose by 16% at most. Abstract: We report on an experimental investigation of radiation induced static mode degradation in Yb-Ce co-doped pulsed fiber amplifiers. For investigating the impact of irradiation on beam quality, radiation-darkened fibers were irradiated by gamma rays. The laser properties of three types of fibers were investigated. With the pump power increased, static mode degradation appeared: M 2 factor raised significantly and the output beam profile transformed from LP01 into LP11 shape without high-frequency component. The threshold of static mode degradation decreased with irradiation dose, and related to Yb-Ce co-doped fiber compositions. The doping of Ce benefits to the improvement of the static mode degradation threshold: in the case of the Ce concentration increasing by 35.5%, SMD threshold rose by 16% at most.